ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS DITINJAU DARI KEMAMPUAN METAKOGNITIF - Risna Nurmaya Saroh; Redo Martila Ruli (IKIP Siliwangi, 2023)
Mathematical representation ability influenced by metacognitive abilities. This study aims to describe the ability of mathematical representation in terms of students' metacognitive abilities. This research was conducted at a junior high school in Karawang Regency with 39 students in class VIII as research subjects. The research method used is a qualitative approach to the type of phenomenological research. Data in this study were obtained based on research measurement instruments in the form of mathematical representation ability test questions, metacognitive ability questionnaires, and interview guidelines. The data was analyzed using the Miles and Huberman’s methods, which included data reduction, data presentation, and drawing conclusions. Based on the results of data analysis, it can be concluded that students with high metacognitive abilities are able to fulfill the indicators of symbol and image representation very well, and quite good verbal representations, then students with moderate metacognitive abilities are able to fulfill the indicators of image representation well but are good enough for symbolic representation and verbal, as well as for students with low metacognitive fulfillment of symbolic, pictorial and verbal representations that are quite good.